The impact of internal corporate social responsibility on employees' subjective well-being: the case of the Chinese IT industry - Tao, Liu (2022)
This study used a quantitative research method to conduct a web-based questionnaire survey with a sample of employees in the IT industry in China. The data was then analysed through SPSS, and the results were compared with previous studies. The study found that health and safety were the most important factors associated with employees' subjective well-being (job satisfaction) in the Chinese IT industry during the particular period of the epidemic. I-CSR and the dimensions of i-CSR such as health and safety, employment stability, employee empowerment and work-life balance were significantly associated with employees' subjective well-being (job satisfaction).